2020
DOI: 10.1155/2020/5041629
|View full text |Cite
|
Sign up to set email alerts
|

Xuan Bi Tong Yu Fang Promotes Angiogenesis via VEGF‐Notch1/Dll4 Pathway in Myocardial Ischemic Rats

Abstract: Objective. To investigate the effect of Xuan Bi Tong Yu Fang (XBTYF) on angiogenesis via the vascular endothelial growth factor- (VEGF-) Notch1/delta-like 4 (Dll4) pathway. Materials and Methods. Sixty Sprague-Dawley rats were randomly divided into six groups: control, sham-operated, myocardial ischemia model, and XBTYF treatment at 3.2, 1.6, and 0.8 g/kg. Electrocardiography was performed to evaluate the successful establishment of the model. Hematoxylin-eosin staining and transmission electron microscopy wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Some efforts have been made to recognize available inhibitors of Notch1 signaling in ECs. Apart from resveratrol mentioned above (19), it has been shown that Xuan Bi Tong Yu Fang, a well-known traditional Chinese medical prescription, promotes EC-mediated angiogenesis in rats with myocardial ischemia by inhibiting the Dll4/Notch1 pathway (21). The anticoagulant drug, sulodexide (22), and the vasodilator, pentoxifylline (23), have also been found to inhibit the Dll4/Notch1 pathway to affect angiogenesis in mouse proepicardial explant cultures.…”
Section: Role Of Notch1 Signaling In Atherosclerosismentioning
confidence: 99%
“…Some efforts have been made to recognize available inhibitors of Notch1 signaling in ECs. Apart from resveratrol mentioned above (19), it has been shown that Xuan Bi Tong Yu Fang, a well-known traditional Chinese medical prescription, promotes EC-mediated angiogenesis in rats with myocardial ischemia by inhibiting the Dll4/Notch1 pathway (21). The anticoagulant drug, sulodexide (22), and the vasodilator, pentoxifylline (23), have also been found to inhibit the Dll4/Notch1 pathway to affect angiogenesis in mouse proepicardial explant cultures.…”
Section: Role Of Notch1 Signaling In Atherosclerosismentioning
confidence: 99%
“…Danhong injection (DHI) could mitigate inflammation associated with MI through inhibiting NF-κB nuclear translocation and regulating miRNAs, thus improving cardiac function in myocardial infarction rats . Shengmai injection (SMI) could increase cell viability, prevent cell apoptosis, and increase PI3K and p-Akt expression in H9c2 cardiomyocytes injured by doxorubicin (Li et al, 2020c). Furthermore, it has been reported that the SMI-driven reduction in apoptosis was related to the change in the Bcl-2/Bax ratio (Liu et al, 2018a).…”
Section: Frontiers In Pharmacologymentioning
confidence: 99%